Sensitive high resolution ion microprobe (SHRIMP) detrital zircon geochronology provides new evidence for a hidden Neoproterozoic foreland basin to the Grenville Orogen in the eastern Midwest, U.S.A. - Santos, J.; Hartmann, L.; McNaughton, Neal; Easton, R.; Rea, R.; Potter, P. (National Research Council Canada, 2002)
A sensitive high resolution ion microprobe (SHRIMP) was used in combination with backscattered electron (BSE) and cathodoluminescence (CL) images to determine the age of detrital zircons from sandstones in the Neoproterozoic Middle Run Formation of the eastern Midwest, United States. Eleven samples from seven drill cores of the upper part of the Middle Run Formation contain detrital zircons ranging in age from 1030 to 1982 Ma (84 analyses), with six distinctive modes at 1.96, 1.63, 1.47, 1.34, 1.15, and 1.08 Ga. This indicates that most, but not all, of the zircon at the top of the Middle Run Formation was derived from the Grenville Orogen. The youngest concordant detrital zircon yields a maximum age of 1048 ± 22 Ma for the Middle Run Formation, indicating that the formation is younger than ca. 1026 Ma minus the added extra time needed for later uplift, denudation, thrusting, erosion, and transport to southwestern Ohio. Thus, as judged by proximity, composition, thickness, and geochronology, it is a North American equivalent to other Neoproterozoic Grenvillian-derived basins, such as the Torridon Group of Scotland and the Palmeiral Formation of South America. An alternate possibility, although much less likely in our opinion, is that it could be much younger, any time between 1048 ± 22 Ma and the deposition of the Middle Cambrian Mount Simon Sandstone at about 510 Ma, and still virtually almost all derived from rocks of the Grenville Orogen.